KEMATANGAN PENGAMBILAN KEPUTUSAN KARIER DITINJAU DARI DUKUNGAN TEMAN SEBAYA - Ahlun Tiara; Dini Rahkmawati; Chr. Argo Widiharto (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This research is motivated by the importance of high school students ability to make mature career decisions, especially amidst the many complex future choices and the high number of unemployed people. One factor that may influence is assistance from peer support, so it can function as a source of information and emotional support. This study aims to determine the effect of peer support on the maturity of career decision-making in grade XI students of SMA Negeri 1 Sayung Demak. The approach used is quantitative with a correlational design. The research sample amounted to 207 students with a saturated sampling technique. Data collection was carried out using a Likert scale questionnaire that has been tested for validity and reliability. Dat analysis used simple linear regression with the help of the SPSS program version 25. The results of the analysis produced a regression equation Y = 33.141 + 0.580X + e. The t-test showed a calculated t value of 9.318 with a significance of 0.000 < 0.05, so the hypothesis was accepted. On the other hand, the correlation coefficient of 0.0545 indicates a moderate relationship, and the determination coefficient of 0.0298 indicates that peer support contributes 29.8% to the maturity of career decision-making. Therefore, it can be concluded that peer support has a positive and significant effect on the maturity of students career decision-making.